We are given the following equation
![3x^2+7x+14=-7x](https://img.qammunity.org/2023/formulas/mathematics/college/h6zbqhbuuao9gihr9mxq4wznank9jqi3fd.png)
Let us solve the equation for x.
First of all, rearrange the equation so that all the terms are on the left side of the equation
![\begin{gathered} 3x^2+7x+14=-7x \\ 3x^2+7x+7x+14=0 \\ 3x^2+14x+14=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zquh72tbn3cfedzy685i1blqiml1u5ikzl.png)
Recall that the standard form of a quadratic equation is given by
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
Comparing the given equation with the standard form, the coefficients are
a = 3
b = 14
c = 14
Recall that the quadratic formula is given by
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/jr19ixi2zltkocy82qhxfiop5lyv4hzbkm.png)
Let us substitute the values of coefficients and simplify
![\begin{gathered} x=\frac{-14\pm\sqrt[]{14^2-4(3)(14)}}{2(3)} \\ x=\frac{-14\pm\sqrt[]{196^{}-168}}{6} \\ x=\frac{-14\pm\sqrt[]{28}}{6} \\ x=\frac{-14+\sqrt[]{28}}{6},\: \: x=\frac{-14-\sqrt[]{28}}{6} \\ x=-1.5,\: \: x=-3.2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ig8yjg4j027ybui91zrpodh40a70vo3zr7.png)
Therefore, the solution of the equation is
![x=\mleft\lbrace-1.5,-3.2\mright\rbrace](https://img.qammunity.org/2023/formulas/mathematics/college/9gdes5xina57mmmtx6d6o1bwiak3o5gxb9.png)